2018
DOI: 10.3171/2018.3.peds17701
|View full text |Cite
|
Sign up to set email alerts
|

Changes in resting-state connectivity in pediatric temporal lobe epilepsy

Abstract: OBJECTIVEFunctional connectivity magnetic resonance imaging (fcMRI) is a form of fMRI that allows for analysis of blood oxygen level–dependent signal changes within a task-free, resting paradigm. This technique has been shown to have efficacy in evaluating network connectivity changes with epilepsy. Presurgical data from patients with unilateral temporal lobe epilepsy were evaluated using the fcMRI technique to define connectivity changes within and between the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…Here we addressed the functional brain connectivity of adult animals with SE in the developing brain. Although connectivity in the default mode network is frequently reported as altered in epileptic patients as well as animal models with epilepsy induced in adulthood ( Centeno and Carmichael, 2014 ; Cui et al, 2018 ; Gill et al, 2017 ; Grassia et al, 2018 ; Haneef et al, 2014 ), our analysis did not show any significant change in the connectivity of these regions. The reason for this discrepancy might be the low number of subjects in the fMRI analysis, which involved only seven SE animals and seven controls due to the presence of the artefacts from the urethane sleep-like state transitions and motion-related artefacts that we were not able to subtract from the fMRI signal of the remaining animals.…”
Section: Discussioncontrasting
confidence: 80%
“…Here we addressed the functional brain connectivity of adult animals with SE in the developing brain. Although connectivity in the default mode network is frequently reported as altered in epileptic patients as well as animal models with epilepsy induced in adulthood ( Centeno and Carmichael, 2014 ; Cui et al, 2018 ; Gill et al, 2017 ; Grassia et al, 2018 ; Haneef et al, 2014 ), our analysis did not show any significant change in the connectivity of these regions. The reason for this discrepancy might be the low number of subjects in the fMRI analysis, which involved only seven SE animals and seven controls due to the presence of the artefacts from the urethane sleep-like state transitions and motion-related artefacts that we were not able to subtract from the fMRI signal of the remaining animals.…”
Section: Discussioncontrasting
confidence: 80%
“…The most commonly used method is the seed-based analysis, which estimates changes in BOLD signal of a particular region of interest to the whole-brain connectivity. Several pediatric studies have demonstrated evidence that patterns of RSN can change in various epileptic diseases, such as absence [113] and partial epilepsy [114], including temporal lobe epilepsy [115], showing mostly decreased connectivity compared to a group of healthy control subjects. The connectivity changes observed in such group analyses encouraged investigators to apply rs-fMRI in the clinical practice and report preliminary experiences in individual patients [116][117][118].…”
Section: Resting-state Fmrievaluation Of Brain Connectivitymentioning
confidence: 99%
“…Despite our limited understanding of the network effects of epilepsy, the potential clinical utility is expanding. Direct applications are most apparent in surgical epilepsies where network approaches have already demonstrated utility in identifying the epileptogenic region for resection and predicting postoperative outcomes of both seizure freedom and functional deficits . Pertaining to the nonsurgical childhood epilepsies, an understanding of network effects has the potential to yield new biomarkers including, as already demonstrated in one study, the possibility of predicting medication refractoriness .…”
Section: Discussionmentioning
confidence: 99%